Identification pyroptosis-related gene signature to predict prognosis and associated regulation axis in colon cancer - Zhou, Kexun; Gu, Xuyu; Tan, Huaicheng; Yu, Ting; Liu, Chunhua; Ding, Zhenyu; Liu, Jiyan; Shi, Huashan (Frontiers in Pharmacology, 2022)
Pyroptosis is an important component of the tumor microenvironment, associated with the occurrence and progression of cancer. However, the expression of pyroptosis-related genes and its impact on the prognosis of colon cancer (CC) remains unclear. Here, we constructed and validated a pyroptosis-related genes signature to predict the prognosis of patients with CC. Public data source was obtained to screen out candidate genes for further analysis. Various methods were combined to construct a robust pyroptosis-related genes signature for predicting the prognosis of patients with CC. Based on the gene signature and clinical features, a decision tree and nomogram were developed to improve risk stratification and quantify risk assessment for individual patients.The pyroptosis-related genes signature successfully discriminated CC patients with high-risk in the training cohorts. The prognostic value of this signature was further confirmed in independent validation cohort. Multivariable Cox regression and stratified survival analysis revealed this signature was an independent prognostic factor for CC patients. The decision tree identified risk subgroups powerfully, and the nomogram incorporating the gene signature and clinical risk factors performed well in the calibration plots. Pyroptosis-related genes signature was an independent prognostic factor, and can be used to predict the prognosis of patients with CC.